A study on computer viruses attacks and the way to cure them / Shukor Sanim Mohd Fauzi - Mohd Fauzi, Shukor Sanim (2003)
Many organizations and users are working hard to secure themselves from the growing threats of computer viruses, Trojan horses, worms, and other malicious codes. Computer viruses attacks are problems created by men or women and they are problems that can also be controlled by men or women. In the end, it is basically a war between virus writers and virus fighters. There are bright minds on both sides, and it looks like this fight is not going to end. This research intends to find the pattern of computer viruses attacks and perform a prediction on the next occurrence of virus. Other than that, this research also will propose a new way to cure from computer viruses attacks. The findings of this research are hope be able to shed some light for all of us.